2018
DOI: 10.12965/jer.1836396.198
|View full text |Cite
|
Sign up to set email alerts
|

Maximal isometric handgrip strength: comparison between weight categories and classificatory table for adult judo athletes

Abstract: The aims of this study were to compare the maximal isometric handgrip strength of judo athletes from different weight categories and to create a classificatory table for this test. A total of 406 athletes had their maximal isometric handgrip strength measured, following standardized recommendations. Absolute and relative values were calculated for each hand and for the sum of both hands. Weight categories were compared through a one-way analysis of variance, followed by Tukey test. The effect size was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 19 publications
2
39
1
2
Order By: Relevance
“…Allometry has been commonly used in physical assessment, but it is still neglected when HGS is analyzed. Some studies have investigated the use of allometry in HGS data (Karavelioglu et al, 2017;Pua, 2006;Vanderburgh et al, 1995), especially in athletes, but many others studies have been using the ratio standard (Branco et al, 2018;Franchini et al, 2018;Franchini et al, 2020). Vanderburgh et al (1995) was one of the first to investigate the use of allometry in HGS data and found an allometric exponent of 0.54 for male university students, a value very close to what was found in the present study (b=0.56).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Allometry has been commonly used in physical assessment, but it is still neglected when HGS is analyzed. Some studies have investigated the use of allometry in HGS data (Karavelioglu et al, 2017;Pua, 2006;Vanderburgh et al, 1995), especially in athletes, but many others studies have been using the ratio standard (Branco et al, 2018;Franchini et al, 2018;Franchini et al, 2020). Vanderburgh et al (1995) was one of the first to investigate the use of allometry in HGS data and found an allometric exponent of 0.54 for male university students, a value very close to what was found in the present study (b=0.56).…”
Section: Discussionsupporting
confidence: 86%
“…Recently, a classificatory table for adult judo athletes was proposed according to the HGS magnitude in absolute and relative terms (ratio standard) (Franchini et al, 2018); however, our data suggest that ratio standard is not the best scaling method because it does not remove adequately the BM effect. In this sense, the normative values should be analyzed with caution when comparing judo athletes with different BM categories.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our assumption is that light-weight judokas will score higher on short high-intensity movements, and the heavy-weight judokas will have absolute higher scores on maximal strength. 13,23 No differences in psychological performance characteristics are expected. If there are clear differences between light-and heavy-weight judokas, the training of judokas can be adapted to these specific performance characteristics in order to increase performance development towards the elite level.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of research is now available investigating the physical and physiological factors differentiating more (i.e., medal-winning), from less (i.e., non-medallists) successful athletes in various individual and team-based field sports [6,[8][9][10][11][12], and even across weight divisions [13]. In combat sports, recent evidence has demonstrated that physical performance qualities contribute to success in Brazilian jiujitsu [14], taekwondo [10] and mixed martial arts [15].…”
Section: Introductionmentioning
confidence: 99%